2011
DOI: 10.1016/j.intimp.2011.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis-like disease in C57BL/6 mice infected with mouse hepatitis virus A59

Abstract: Mouse hepatitis virus A59 (MHV A59) induces autoantibodies (autoAb) to fumarylacetoacetate hydrolase (FAH), a soluble cytosolic enzyme present in the liver and kidneys, in various mouse strains. The aim of this work was to amplify and diversify the autoimmune response restricted to FAH through the use of the exogenous adjuvant called PADRE. Accordingly, C57BL/6 mice were chosen, because these animals respond to PADRE better than other mouse strains. Results presented herein indicate that, surprisingly, C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
5
16
0
Order By: Relevance
“…Similarly, Kuo et al found a marked elevation of serum alpha-fetoprotein with severe jaundice as an initial manifestation of AIH [21]. The fumarylacetoacetase, which was also identified to be upregulated in our AIH mice, was also verified by its autoantibody in sera of a mouse hepatitis model [22]. The findings brought into correspondence with our experimental result which showed an increase in AIH model compared to the control group.…”
Section: Resultssupporting
confidence: 86%
“…Similarly, Kuo et al found a marked elevation of serum alpha-fetoprotein with severe jaundice as an initial manifestation of AIH [21]. The fumarylacetoacetase, which was also identified to be upregulated in our AIH mice, was also verified by its autoantibody in sera of a mouse hepatitis model [22]. The findings brought into correspondence with our experimental result which showed an increase in AIH model compared to the control group.…”
Section: Resultssupporting
confidence: 86%
“…[88][89][90] Another pathogenic strain, MHV-A59 (derived from normal mouse liver cell line-NCTC-1469 or from L2 cells) induced fulminant hepatitis as well as autoimmunity in susceptible C57BL/6 mice with formation of autoantibodies (autoAb) to fumarylacetoacetate hydrolase (FAH), a soluble cytosolic enzyme present in the liver and kidneys. [91] The acute liver injury (after 3-5 days infection) induced by MHV-A59 is associated with an increase level of IL-6, TNF-α and IL-17 in mice. [89] In contrast, the non-pathogenic strain isolated from persistently infected YAC lymphoid cell line (YAC-MHV3) does not induce an acute lethal disease but only subclinical infection in mice.…”
Section: Mouse Hepatitis Virus Type 3 (Mhv3) Induced Acute Hepatitismentioning
confidence: 99%
“…HLA-DR binding epitope) [111] applified the MHV-induced AIH [110]. These data indicate that virus-infections can promote autoimmunity in the liver and that additional exogenous stimuli can accelerate this process.…”
Section: Pathogens and Autoimmune Hepatitis mentioning
confidence: 73%
“…Recently, Aparicio et al generated a further model by infecting wild-type C57BL/6 mice with the mouse hepatitis virus A59 (MHV) and thereby generating autoantibodies to fumarylacetoacetat hydrolase (FAH), which is expressed in the liver and kidney [110]. The mice displayed features of AIH, including hypergammaglobulinemia, elevated serum aminotransferases, hepatic cellular infiltrations, and antibodies to liver autoantigens.…”
Section: Pathogens and Autoimmune Hepatitis mentioning
confidence: 99%